Discovering Dynamics of Diminishing Resistance in Kazuo Ishiguro's Never Let Me Go (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This research paper examines the lack of resistance towards the unjust and inhuman treatment of clones, despite the obvious reasons for opposition in Kazuo Ishiguro’s Never Let Me Go. The dystopian society depicted in the narrative moves around clones Kathy, Ruth, and Tommy being created only for organ donation to humans. Given the harsh and unfair treatment they endure, one would expect significant resistance from the clones. However, this study argues that definite dynamics repress their aptitude to rebel and instead admit their predetermined providence. Hence, relying on the theoretical concepts of indoctrination and hegemony proposed by Louis Althusser and Antonio Gramsci, this paper unfolds how individuals can be influenced and conditioned to adopt values and beliefs that align with the dominant ideology, even if it contradicts their own well-being and autonomy. Therefore, this article gives emphasis on the importance of critically examining the impact of ideology and socialization on individuals’ attitudes and behaviors.